Docking and Dynamics Study of Phytochemicals as Potent Inhibitors against SARS-CoV-2 Main Protease - Palla Ramprasad; Arunkumar Babu; Suveena Sukumaran (Journal of Molecular Docking, 2022)
Coronavirus Infectious Disease-19 (COVID-19) caused by coronavirus 2 is a global health hazard. The lack of medications against the disease is a major concern of the research community today. Severe Acute Respiratory Syndrome Coronavirus 2 Main Protease (SARS-CoV-2 MPro) is the most extensively studied protein responsible for spreading disease. Several plant-based products are utilized to treat the disease's symptoms. Here, we have attempted to screen 377 phytocompounds against the target computationally. We have sorted eight best-pose compounds based on docking studies for further analysis. Lipinski and Adsorption, Distribution, Metabolism, Elimination/Toxicity (ADME/T) properties were also evaluated to assess the drug-like properties and toxicity of the screened compounds. Finally, we discovered Coruscanone to be the most effective lead compound for the target. The best complex was further undertaken for dynamic simulation. RMSD, RMSF, h-bond, and Rg were analyzed and studied related to the reference compound. The study additionally continues to elucidate its inhibitory action via in vitro studies.